2016
DOI: 10.1016/j.ijcha.2015.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin induced heart failure: Phenotype and molecular mechanisms

Abstract: Long term survival of childhood cancers is now more than 70%. Anthracyclines, including doxorubicin, are some of the most efficacious anticancer drugs available. However, its use as a chemotherapeutic agent is severely hindered by its dose-limiting toxicities. Most notably observed is cardiotoxicity, but other organ systems are also degraded by doxorubicin use. Despite the years of its use and the amount of information written about this drug, an understanding of its cellular mechanisms is not fully appreciate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
195
0
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(231 citation statements)
references
References 103 publications
(128 reference statements)
8
195
0
12
Order By: Relevance
“…In addition, the LVs of DOX‐treated rats demonstrated morphological and ultrastructural changes including sever cytoplasmic vacuolization, mitochondrial damage, and myofibrillar loss. All these changes have previously been described in similar animal models, as well as in the failing human heart, and were explained by multiple interconnected mechanisms including increased cell apoptosis, impaired Ca +2 homeostasis, down‐regulation of the contractile proteins synthesis, myocyte atrophy, and compensatory hypertrophy …”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…In addition, the LVs of DOX‐treated rats demonstrated morphological and ultrastructural changes including sever cytoplasmic vacuolization, mitochondrial damage, and myofibrillar loss. All these changes have previously been described in similar animal models, as well as in the failing human heart, and were explained by multiple interconnected mechanisms including increased cell apoptosis, impaired Ca +2 homeostasis, down‐regulation of the contractile proteins synthesis, myocyte atrophy, and compensatory hypertrophy …”
Section: Discussionmentioning
confidence: 67%
“…In addition, the LVs of DOX-treated rats demonstrated morphological and ultrastructural changes including sever cytoplasmic vacuolization, mitochondrial damage, and myofibrillar loss. All these changes have previously been described in similar animal models, as well as in the failing human heart,3,32-34 and were explained by multiple interconnected mechanisms including increased cell apoptosis, impaired Ca +2 homeostasis, down-regulation of the contractile proteins synthesis, myocyte atrophy, and compensatory hypertrophy 8,33,[44][45][46]. On the other hand, numerous studies have shown that DOX administration activates both intrinsic and extrinsic cell death in severalF I G U R E 4 Doxorubicin (DOX) increases the activity of ERK, p-P38 MAPKs and inhibits mTOR activity in the left ventricle (LVs) of rats (A, C) and cultured cardiomyocytes (B, D) but enhances JNK activity in cultured cardiomyocytes (D).…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…The function and integrity of mature cardiomyocytes are mainly defined by their high energy requirements . In line with this, heart failure is linked to impaired mitochondrial function and disrupted lipid metabolism . Mitochondrial functioning in cardiomyocytes can be directly interrupted by reactive oxygen species derived from the reduction of DOX to 7‐deoxy‐doxorubicinone , intracellular iron accumulation, and loss of the iron balance .…”
Section: Discussionmentioning
confidence: 99%
“…Наи-более эффективным представителем этой группы являет-ся доксорубицин. Вызываемая им КМП характеризуется одинаковым симптомокомплексом у людей и животных [1,2], проявляющимся в виде систолической дисфункции (СД) левого желудочка (ЛЖ) и хронической сердечной недостаточности (ХСН) [3]. КМП, вызываемая ежене-дельным введением доксорубицина, развивается посте-пенно.…”
unclassified